Delivering Dynamic Civics Learning Through the TPACK Approach at the Elementary School Level - Al Fikri, Muhammad Arif (Jurnal keilmuan dan Kependidikan dasar, 2026)
This research aims to analyze the implementation of the Technological Pedagogical Content Knowledge (TPACK) approach in creating dynamic Civic Education (PKn) learning at the elementary school level and to identify the challenges educators face. The method used is a Systematic Literature Review (SLR) that reviews 15 selected research articles published between 2020 and 2026. Literature sources were obtained from Google Scholar, DOAJ, SINTA, and Garuda databases using the keywords "TPACK", "Citizenship Education" (Civic Education), and "elementary school Civics learning". The review findings indicate that the TPACK approach has transformative potential for Civics learning, especially when combined with Project-Based Learning and Contextual Teaching and Learning models, which have been shown to improve students' cognitive and affective learning outcomes and their motivation to learn. Moreover, TPACK plays an important role in strengthening students' character and digital citizenship. This review also highlights the integration of artificial intelligence (AI), such as ChatGPT, as a future instructional assistant. Nevertheless, several key challenges were identified, including low digital literacy among teachers (particularly senior teachers), limited technological infrastructure, difficulties in time management when using project-based models, and the gap between teachers' content mastery and their integration of pedagogy and technology.